Pembelajaran Eksperiensial untuk Mengembangkan Kreativitas Gerak Tari Tradisi di Kelas 7A SMPN 10 Malang - Atika, Yolanda Deby Marta; D.P., Endang Wara Suprihatin (Universitas Pahlawan Tuanku Tambusai, 2025)
The experiential learning method gives students the opportunity to feel and experience knowledge through activities. In the Phase D Learning Achievement related to collaboration in exploring dance movements, movement creativity is needed so that the performance appears aesthetically pleasing. The research subjects were 7A grade students of SMPN 10 Malang, who had the lowest average score compared to all other 7th-grade students. The purpose of this study was to enhance students’ creativity in dance movements through the experiential learning method. The researcher applied the Classroom Action Research (CAR) method, which consisted of two cycles, where each cycle included planning, implementation, observation, and reflection. Data collection used qualitative methods for descriptive data and quantitative methods for numerical data. The research results showed that: a) in the first cycle, 5 students achieved mastery with a percentage of 18.51%; b) in the second cycle, the number of students achieving mastery increased by 24 students, reaching 88.8%. Therefore, project-based learning was effective in improving students' learning outcomes in traditional dance movement creativity in class 7A of SMPN 10 Malang.